2022
DOI: 10.3389/fmicb.2022.874582
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Distribution Patterns of Phyllosphere Microbial Communities and Their Contribution to Silage Fermentation of Kobresia pygmaea Along the Elevation Gradient on the Tibetan Plateau

Abstract: The study aimed to reveal altitudinal distribution patterns of phyllosphere microbial communities and silage fermentation of Kobresia pygmaea along the elevation gradient on the Tibetan Plateau. The K. pygmaea was individually collected from 2,500, 3,000, 4,000, 4,500, and 5,000 m above sea level (a.s.l.) on the Tibetan Plateau and ensiled for 60 days, respectively. The phyllosphere bacterial diversity increased while fungal diversity decreased along the elevation gradient, and bacterial and fungal richness sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“… Vacher et al (2016) demonstrated that the higher dispersal ability of bacteria and higher sensitivity of fungi to temperature variations might account for the bigger response of phyllosphere fungal communities to elevation gradient than bacterial communities. In the present study, the elevation gradients did not affect the fungal Shannon index in fresh oat ( p > 0.05), which was consistent with the reports by Yang X. et al (2022) , who also detected similar soil fungal Shannon index across elevation gradients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“… Vacher et al (2016) demonstrated that the higher dispersal ability of bacteria and higher sensitivity of fungi to temperature variations might account for the bigger response of phyllosphere fungal communities to elevation gradient than bacterial communities. In the present study, the elevation gradients did not affect the fungal Shannon index in fresh oat ( p > 0.05), which was consistent with the reports by Yang X. et al (2022) , who also detected similar soil fungal Shannon index across elevation gradients.…”
Section: Discussionsupporting
confidence: 93%
“…The inconsistency of phyllosphere microbial diversity patterns across elevations could be attributed to changing environmental factors induced by elevational variables ( Yang N. et al, 2022 ). Yang X. et al (2022) found that the phyllosphere bacterial and fungal richness showed a unimodal distribution, phyllosphere fungal diversity decreased while the phyllosphere bacterial diversity increased along the elevational gradient. We observed the bimodal distribution of fungal and bacterial richness in fresh oat along the elevation gradient (2852–4447 m a.s.l).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations